Effect of Existing and Imposed Vaccination on Body Weight Against Gumboro in Broiler under Farm Condition - Paul, B.K.; Das, S.K.; Badhy, S.C.; Amin, M.R.; Amin, K.M.R.; Banik, S.C. (International Journal of Poultry Science, 2004)
To asses the effect of existing and imposed vaccination programme on body weight in broiler under farm condition in Bangladesh an experiment was conducted in the Department of Medicine, Faculty of Veterinary Science, Bangladesh Agricultural University, Mymensingh-2202, Bangladesh from August to September 2003. Seven different broiler farms in the Sherpur District were taken dividing the farms into two groups-Group I: for existing vaccination and Group II: for imposed vaccination. From all the farms blood samples were collected before vaccination to check maternal antibody level. Infected as well as dead birds were undergone through necropsy examination properly in spot as well as BLRI, Savar, Dhaka. The present study reveled that the birds survived the diseases lost ranges from 1190-1320g (Group I) than those did not face Gumboro 1585-1620g (Group II). Thus, there is a significant variation in body weight in Gumboro affected broilers due to existing and imposed vaccination programme under farm condition.